Ijtihad dalam Pandangan Muhammad Asad - M. Tabah Rosyadi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
This article explains that an finding the truth of law, besides using textual method of al-Qur’an and Sunnah, Asad hence rational method (ijtihādī). Asad also a firm hold the contextual method According to his interpretation, Islam is intellectual movement, because Islam have peeped out the definitive idea and clear agenda. Asad really trusts in the mind as method to look for the truth. He expresses that even to choose the religion, people have to be guided by their mind, and with that mind people will be able to know how far the religion can fulfill the human being requirement, physical or spiritual.